The Impact of Virtual and Augmented Reality on Enhancing Higher Order Thinking Skills (HOTS) of Students: A Bibliometric Analysis Study - Maulana, Iwan; Siswandari, Siswandari; Gunarhadi, Gunarhadi; Efendi, Agus (Angstrom Centre of Education, 2024)
This paper presents a bibliometric analysis study focusing on the impact of virtual and augmented reality (VR/AR) technologies on the enhancement of Higher Order Thinking Skills (HOTS) among students. In recent years, VR/AR has gained significant attention in educational contexts due to its immersive and interactive nature, offering unique opportunities for fostering critical thinking, problem-solving, and creativity among learners. This research aimed to systematically analyze the existing literature on the subject to identify trends, key themes, influential authors, and significant research gaps. Through comprehensive bibliometric analysis, encompassing citation networks, co-authorship patterns, and thematic clusters, this study provides insights into the evolution and current state of research in the intersection of VR/AR and HOTS enhancement. Furthermore, it seeks to elucidate the theoretical frameworks, methodologies, and pedagogical approaches employed in these studies, shedding light on effective strategies for integrating VR/AR technologies into educational practices. By synthesizing and evaluating the scholarly output in this field, this research contributes to the understanding of the potential of VR/AR in promoting HOTS development and informs future directions for research and practice in educational technology and curriculum design.